PELAKSANAAN PEMBELAJARAN INKLUSI TINGKAT SMA DAN SMK DI PROVINSI SUMATERA BARAT - Rahmi, Aulia; Damri, Damri (STKIP Pesisir Selatan, 2021)
This study originated from the findings of researchers who indicated that there were problems in the implementation of inclusive learning in 91 SMA and SMK in West Sumatra. This study aims to examine the suitability of Permendiknas Number 70 of 2009 with the implementation of learning in schools. This study uses a qualitative method. Data collection techniques in the form of observation, interviews and documentation. The research setting was at 4 SMA and SMK in West Sumatra, with informants consisting of 10 people, 1 principal, 2 curriculum representatives, 3 subject teachers, 2 BK teachers, and 2 GPK people from four different SMA and SMK. The results of the study found three general findings and four specific findings. Namely the implementation of identification, assessment, PPI, flexible curriculum, evaluation and assessment of learning outcomes. The obstacles encountered are grouped into four sections, from the government, from school leaders, from teachers, and from students. The government has issued guidelines containing guidelines and regulations. It turned out that the results were not in accordance with the phenomena in the field, and there was a paradox (the expectations were not matched with the reality that had happened). Therefore the researchers suggest that the implementation of inclusive learning in SMA and SMK consistently implement the Minister of Education Regulation Number 70 of 2009. If the organizers of inclusive learning are not consistent, the implementation of inclusive learning is just wishful thinking